(3GYJbGO GdEeGejIs - (3Ydj Hf GdMSjf Hf HCHhjI GdbeQs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ai UaI EYJbGO GdEeGejI bGd GdTjN Ydi Hf GdMSjf Hf HGHhjI GdbeQ GdeUfa dgPG GdcJGH CYde EYJbGOfG ai GdJhMjOGf Gddg JYGdi hMO CMO s
(3BNQgG (B:s
(3hbO CNQLJ GdNHQ ai Pdc eSJajVkG dTQMI ai cJGH GdJhMjO hcJGHkG ai Pdc HeTjFI Gddg hYhfg Ef TGA Gddg JYGdi hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eOjfI GdYde (B_ (3GdcGXejI (B(325) s
Keywords: (3GdeLGejYs